(untitled) (Bangladesh Journal of Animal Science, 2019)
The research work was carried out to evaluate the food-feed competitive efficiency of Moringa fodder in the Active Brahmaputra-Jamuna Floodplain Agro-Ecological Zone (ABJF-AEZ) of Bangladesh. For determining the competitive land use efficiency of Mornga feed (Mf) production, the Moringa fodder was cultivated in Gaibandha district at ABJF-AEZ with four replications. The annual dry matter (DM) yield of Moringa at on-farm condition was the height (26.67 ton/ha) and it was varied significantly (P<0.05) with on-station condition. Comparing the Moringa fodder with available cash crop, the cost of production of Moringa was higher than that of other two cropping system like Boro-fellow-Jute (BFJ) and Boro-Fellow-Matikalai (BFM) but the gross return of Moringa cultivation was Tk.186.3 thousand, it was about five times higher income than existing cash crop. For determining the impacts of Mf on milk production and their quality, twelve local cows of third or fourth parity after 1 to 2 weeks of calving in Gaibandha Sadar Upazila were selected and divided into three dietary groups having four animals in each considering their live weight and ante-diet daily milk yield. During 50 days feeding period all experimental cows were fed freshly threshed rice straw and keeping randomly a group under on farm practice that received supplementation of conventionally mixed concentrates (CMC), the other two groups of cows were either received a commercial cattle feed available at the market or Mf replacing conventional concentrate supplements. Mf produced significant amount of milk (1.64 kg/day) and meat (441.3 g/day) followed by commercial cattle feed (1.1 kg/day and 128.2 g/day) and CMC (0.73 kg/day and 48.4 g/day), respectively. It was also indicated that Mf is better than market feed for the increase of milk yield and live weight gain. So, Mf is an unbeatable animal feed to increase the productivities of cows. Bang. J. Anim. Sci. 2019. 48 (1): 36-41